Behavior of Reinforced Concrete Beams with Openings: A Review - Wrya Abdullah; Omer Ahmed (Emerging Technologies and Engineering Journal)
This paper reviews the effects of openings in reinforced concrete (RC) beams and their effects on the RC beams' ability to bear loads. RC beams may have openings due to the advancement of construction techniques and the rise of supplies and requirements during construction. The paper reviews the effects of opening sizes, locations, and shapes on the behavior of RC beams. It is found that the openings weaken the beam's overall resistance. Also, the openings in the shear zones have a bigger impact than the bending zones, making the beam more brittle during failure. Additionally, regarding the members’ overall energy loss, circular openings are preferable over rectangular and square openings. It is also found that the beam's opening results result in shorter chord distances; therefore, rectangular openings work better horizontally than vertically to maintain a balance between compression and tension zones in the beam. Finally, the size of the openings inversely affects the strength and behavior of the RC beams.